2008
DOI: 10.1111/j.1755-6724.2008.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Influence of Crystallizing Latent Heat on Cooling‐Crystallizing Process of a Granitic Melt and Its Geological Implications

Abstract: Based on the theory of thermal conductivity, in this paper we derived a formula to estimate the prolongation period ( d t~) of cooling-crystallization process of a granitic melt caused by latent heat of crystallization as follows:where TM is initial temperature of the granite melt, TC crystallization temperature of the granite melt, C p specific heat, dtd cooling period of a granite melt from its initial temperature ( T~I ) to its crystallization temperature (Tc), QL latent heat of the granite melt.The cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This might be correlated with the high heat production rate of the Nannihu pluton (Figure 5). Usually, high heat production rate of granites can slowly release a large amount of heat, which prolongs the crystallization process of granite and promotes the migration rate of ore‐forming fluids and materials, further forming the word‐class Mo‐W polymetallic Nannihu deposit (Liu et al, 2023; Mao et al, 2011; Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be correlated with the high heat production rate of the Nannihu pluton (Figure 5). Usually, high heat production rate of granites can slowly release a large amount of heat, which prolongs the crystallization process of granite and promotes the migration rate of ore‐forming fluids and materials, further forming the word‐class Mo‐W polymetallic Nannihu deposit (Liu et al, 2023; Mao et al, 2011; Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported zircon U-Pb ages (closure temperature more than 900 C) of the Luanchuan granitoids with major age peaks at $147 Ma and $110 Ma, which are all interpreted as the crystallization ages of these granitoids (Xue et al, 2018;Yang et al, 2019) Nannihu deposit (Liu et al, 2023;Mao et al, 2011;Zhang et al, 2008). Han et al (2015), He (2015), Li et al (2012), Meng et al (2012), Qi (2014), Qian et al (2022), Tang et al (2021), Wang et al (2019), Xue (2017), Xue et al (2018), Yang, Wang, et al (2012), Yang, Li, and Chen (2012) Yang et al (2019), Zhang (2014), Zhang (2015), Zhang, Cao, et al (2018).…”
Section: Mineralization Of High Heat Production Granitementioning
confidence: 92%